The effectiveness of mimba oil (Azadirachta indica A. Juss) spray disinfectant on alginate impression - Hanoem EH; Wahjuni W; Dinda Dewi Artini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Alginate impression contaminated by saliva and blood could potentially cause cross contamination. To prevent this, the impression has to be disinfected by disinfectant liquid, such as mimba oil. Mimba oil (Azadirachta indica A.Juss) has some chemical content, such as azadirachtin, which is a phenol group used as antibacterial and antimalaria, nimbolide used as antibacterial and antimalarial, and nimbidin used as antibacterial and antifungal. Purpose: The purpose of this study was to find out the most effective concentration of mimba oil as disinfectant to decrease microorganism colony on alginate impression. Methods: Thirty six samples were taken from 9 respondents. This alginate impression was divided into 4 groups: group 1 sprayed with sterile aquadest (as control group), group 2 sprayed with mimba oil 50% for 30 seconds, group 3 sprayed with mimba oil 75% for 30 seconds, group 4 sprayed with mimba oil 100% for 30 seconds. The microorganism colony was counted by colony counter. The sample data then were analyzed with Kolmogorov-Smirnov test, and was tested with Kruskal Wallis test and Mann Whitney test for further analysis. Results: There was significant difference among each group, p = 0.01 (p < 0.05). Conclusion: In conclusion, usage of 50% concentration of mimba oil as disinfectant is effective to decrease microorganism colony on alginate impression.Latar belakang: Cetakan alginat yang terkontaminasi saliva dan darah dapat berpotensi terjadinya infeksi silang. Untuk mencegah hal tersebut, cetakan didisinfeksi dengan bahan disinfektan cair seperti minyak mimba. Minyak mimba (Azadirachta indica A.Juss) memiliki beberapa kandungan kimia, antara lain Azadirachtin yang merupakan kelompok fenol yang memmiliki efek antibakteri dan antimalaria, nimbolide memiliki efek antibakteri dan antimalaria sedangkan nimbidin memiliki efek antibakteri dan antijamur. Tujuan: Tujuan dari penelitian ini adalah untuk menentukan konsentrasi yang paling efektif pada minyak mimba sebagai disinfektan untuk mengurangi jumlah koloni mikroorganisme pada cetakan alginat. Metode: Tiga puluh enam sampel diambil dari sembilan subyek. Cetakan alginat dibagi menjadi empat kelompok: kelompok 1 disemprot dengan aquades steril (kontrol), kelompok 2 disemprot dengan minyak mimba 50% selama 30 detik, kelompok 3 disemprot dengan minyak mimba 75% selama 30 detik, kelompok 4 disemprot dengan minyak mimba 100% selama 30 detik, Jumlah koloni mikroorganisme dihitung menggunakan colony counter. Data dianalisa dengan uji Kolmogorov-Smirnov, dilanjutkan dengan uji Kruskal Wallis dan Mann Whitney. Hasil: Terdapat perbedaan bermakna pada masing-masing kelompok, p = 0,01 (p < 0,05). Kesimpulan: Dapat disimpulkan dengan konsentrasi 50% sebagai desinfektan cetakan alginate telah efektif menurunkan pertumbuhan microorganisme rongga mulut.